HARMONISASI HUKUM HAK CIPTA PROGRAM KOMPUTER DENGAN KULTUR HUKUM MASYARAKAT INDONESIA - Hasbir Paserangi (Faculty of Law, Universitas Diponegoro, 2011)
Indonesia, being a part of international community, cannot neglect the existence of international law . Indonesia, as a consequence, should harmonize international law within municipal law. It also should be done on the rules relating the protection of intellectual property rights. This rules is sourced from international conventions.Implementation of intellectual property right protection ,actually sources from state practice. Relating with it then, the implementation of intellectual property right protection should in-line with the values of nation.